Análisis comparativo del proceso mecánico y manual del descascaramiento de mazorcas de cacao. - Cedeño Reyes, David Samuel (2016)
Cocoa farming is one of the areas of greatest importance for the country, however it is becoming more important to search technology that enable expedite the processes by passing the grain to market such as stage bankruptcy cobs or husks which are generally manually and demand makes enough manpower, but the mechanical method is an option to make this work in less time and still be productive. Considering the above, it conducted this investigation in order to determine the degree of efficiency in the process of scaling (manual and mechanical) of cocoa pods as an index for evaluating productivity in postharvest for them delimited target Specific: determine the productivity index descasacarmiento to determine the process that this lower percentage shell damage cocoa pods, perform an economic analysis of the processes of extraction obtained quintal. The test was carried out Santo Domingo de los Tsáchilas, used a completely randomized design with two treatments in 10 replications, all variables variance analysis and the statistical difference between treatments underwent determined by Duncan test at 95% chance. The manual method presented lower percentage of damaged kernels to 2.5% from 5.3% obtained by the mechanical method, whereas with mechanical means as much Kg / h was obtained with 572.7 and therefore a quintal was obtained in less time than with the conventional method with 4.8 minutes. Besides the mechanical method with a net profit of $ 1,458.26 compared to $ 47.00 the conventional method was obtained. Therefore the most productive method and it was effective as the mechanical method allows more grain extracted once daily and the work rate is constant, which compensates the percentage of grains which could damage in the process